ANALISIS PENGARUH FILLER ABU KULIT KOPI TERHADAP STABILITAS DAN KEPADATAN ASPAL AC – WC NR - Rosyad, Farlin; Pranata, Heru (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2024)
The filler material in the asphalt mixture has the function of increasing the binding capacity of asphalt concrete, so it can improve stability, the filler mixture can fill the voids between the aggregate particles (Fauziah, 2014). If the material is tested for sieve analysis, it must pass the N0 sieve. 200. In this study the author used coffee husk ash as an asphalt filler, coffee husk ash is the result of burning coffee husk waste after grinding coffee, and the characteristics of this coffee husk ash are not fully utilized, so that with this coffee husk ash can be used as a variation in the use of asphalt filler,This research was conducted at the Civil Engineering Study Program Laboratory, Buchori Building 3, Bina Darma University, Palembang, located on Jl. Jendral Ahmad Yani No. 15, 9/10 Ulu, Lintas Ulu 1 sub-district, Palembang city, South Sumatra. The materials used in this research are as follows: The fine aggregate used is stone ash that passes through sieve no. 8 and stuck no. 200, Coarse Aggregate used is split stone/crushed stone retained on filter no. 8, Rubber Asphalt Sir 20 obtained from PT. Sumatra Bitumen Modification, Jl. Across Sumatra Muara Enim – Prabumulih, the coffee skin ash is ground by pounding it so that the coffee skin ash can pass through filter no. 200 and can then be used as a filler. Found in Lubuk Dalam Village, Tanjung Sakti PUMI, Lahat Regency, South Sumatra.Reviewing the test results from variations in coffee skin ash, it can be concluded that the influence of the density value on the optimum coffee skin ash is at a percentage of 2% with a value of 2.242 gr/cc. Meanwhile, based on the Marshall parameter test results in terms of variations in coffee skin ash, it can be concluded that the influence of the stability value on the optimum coffee skin ash is at a percentage of 4% with a value of 1679 kg/cmᵌ.